2019
DOI: 10.3390/nu11071482
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Ingestion, Obesity, and Metabolic-Related Disorders: Results from NHANES, 1999–2014

Abstract: Gut microbiota dysbiosis has been recognized as having key importance in obesity- and metabolic-related diseases. Although there is increasing evidence of the potential benefits induced by probiotics in metabolic disturbances, there is a lack of large cross-sectional studies to assess population-based prevalence of probiotic intake and metabolic diseases. Our aim was to evaluate the association of probiotic ingestion with obesity, type 2 diabetes, hypertension, and dyslipidemia. A cross-sectional study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…The mechanisms by which probiotics assist these processes, are their potential to modulate gut microbiota, competing in the adhesion to intestinal mucosa and epithelium, encouraging mucus production and reinforcing the intestinal barrier [ 197 ]. The establishment of effective formulas and the search for the proper dose, duration, method of administration and long-term effects, are the major challenges for clinical translation of probiotics in diabesity [ 202 ]. Nonetheless, prebiotics and probiotics represent such a promising line of research in the clinical management of this condition.…”
Section: Importance Of Gut Microbiota In Clinical Management Of DImentioning
confidence: 99%
“…The mechanisms by which probiotics assist these processes, are their potential to modulate gut microbiota, competing in the adhesion to intestinal mucosa and epithelium, encouraging mucus production and reinforcing the intestinal barrier [ 197 ]. The establishment of effective formulas and the search for the proper dose, duration, method of administration and long-term effects, are the major challenges for clinical translation of probiotics in diabesity [ 202 ]. Nonetheless, prebiotics and probiotics represent such a promising line of research in the clinical management of this condition.…”
Section: Importance Of Gut Microbiota In Clinical Management Of DImentioning
confidence: 99%
“…Specific gut microbiota, bacterial metabolic pathways and their interactions with human health are new focuses of microbiome research (Proctor, 2019), and understanding of the microbiome is intended to pave the way for future microbiological therapies (Douillard & De Vos, 2019). An increasing number of studies have reported that probiotics in the intestinal tract can maintain intestinal homeostasis by regulating glucose and lipid metabolism, inhibiting the inflammatory response, and improving metabolic disorders (Lau et al, 2019;Plaza-Díaz et al, 2017;Sanders et al, 2019), thus preventing MetS and related complications.…”
Section: Introductionmentioning
confidence: 99%
“…These findings point to a potential use of prebiotic, probiotic or symbiotic products to modify in some way the gut microbiota in individuals prone to obesity and to reduce the impact of this dysbiosis in childhood and later adulthood. Specific probiotic supplements can impinge on lower incidence of obesity and hypertension [9][10][11][12]. Other studies have also shown that specific probiotics impact on weight management in adults [10][11][12] Recent studies have shown that heat-treated bacteria release metabolites or cell components that can display functional actions, such as immunomodulation or antagonism of pathogens [13][14][15].…”
Section: Introductionmentioning
confidence: 99%